Capos, reinas y santos – la narcocultura en México - Günther Maihold (Prof. Dr. Vittoria Borsò, Prof. Dr. Frank Leinen, Jun.-Prof. Dr. Yasmin Temelli, Prof. Dr. Guido Rings, 2013)
In this paper we try to approach what is commonly known as narcoculture from the point of view of three different aspects; on the one hand, we will scrutinize the narcocorrido from its intrinsic and social meaning, the identification keys based on the exaltation of the life of the capos with this counterculture and the government strategies to prevent its dissemination, in the hope of curbing the communication strategies of organized crime. A second aspect to be dealt with is the role of women as reinas and capos in this business and their irruption in the collective imaginary thanks to soap operas. Finally, the devotion to the narcosantos, Malverde and San Nazario will be addressed. It will be possible to reach the conclusion that narcoculture is an expression of the popular and counterculture in the face of modernity, since it is a product of the land, of compadrazgo, of loyalty and is attached to religion. At the same time, it is a product of capitalist modernity because it is the popular fulfillment of the dream of consumerism and freedom. Narcoculture also represents the idea of postmodernity because life culminates in the moment. We believe it is an exaggeration to assert that the narco culture has replaced the corn culture, but the power of rootedness and attraction that emanates from it should not be underestimated.